Effects of Socio-Economic and Political Factors on the Crime Rate in Pakistan - Nabila Asghar; Shazia Qureshi; Muhammad Nadeem (Journal of Political Studies, 2016)
The present study is an attempt to explore the impact of social, economic and political factors and the event of 9/11 on crimes in Pakistan for the period 1984-2013. Three models have been estimated for political, economic and social factors separately. The political factors like corruption, law and order, 9/11 event, have been found to increase crimes, whereas government stability reduces the crimes. The economic factors such as poverty increase crimes whereas foreign remittances and external debt reduce crimes. In social factors human rights, human capital, income inequality and population density increase crimes. In short run, error correction terms indicate that there is convergence towards the equilibrium in all the models in case of any shock. Various diagnostic tests have been applied to confirm the reliability of results which indicate that there is no problem of autocorrelation and heteroscedasticity in the models. The study suggests that in order to mitigate criminal activities policy makers should focus on political, social and economic problems faced by Pakistan.